Pudendal Nerve Neurolysis in Patients Afflicted With Pudendal Nerve Entrapment: A Systematic Review of Surgical Techniques and Their Efficacy - Carlo Giulioni; Giacomo Maria Pirola; Martina Maggi; Lucia Pitoni; Demetra Fuligni; Mattia Beltrami; Vanessa Palantrani; Virgilio De Stefano; Valentina Maurizi; Daniele Castellani; Andrea Benedetto Galosi (International Neurourology Journal, 2024)
To assess the effectiveness and safety of various techniques of pudendal nerve neurolysis (PNN) in patients with pudendal nerve entrapment (PNE). A comprehensive literature search was conducted on May 20th, 2023, using Scopus, PubMed, and Embase databases. Only studies in English involving adults were accepted, while meeting abstracts and preclinical studies were excluded. A total of 34 papers were included. Transperineal PNN emerged as a promising technique, demonstrating significant potential in alleviating pain, restoring erectile function in males, and improving the resolution of urinary stress incontinence in females. Furthermore, the bilateral approach consistently yielded positive outcomes in addressing urinary symptoms. The transgluteal technique appeared particularly suitable for cases of posterior PNE, situated between the sacrospinous ligament and the lesser sciatic foramen. A progressive amelioration of painful symptoms was observed during follow-up. Minimally invasive PNN is evolving and enables decompression along the entire proximal tract up to the Alcock canal, minimizing the risk of comorbidities. In addition to reducing pudendal neuralgia, robot-assisted and laparoscopic approaches determined a reduction in lower urinary tract symptoms and an improvement in erectile function, though further studies are required to corroborate these findings. PNN emerges as an effective treatment for PNE with minimal morbidity. Therefore, PNN should be tailored according to the site of PNE to enhance functional outcomes and improve patient quality of life.